Humic substances: Structure, function and benefits for agroecosystems—a review - TIWARI, Jaya; RAMANATHAN, AL; BAUDDH, Kuldeep; KORSTAD, John (Pedosphere, 2023)
The increasing global demand for food production, often causing excessive use of chemical fertilizers, has led to the deterioration of soil health. Immediate action is required to restore soil health in a sustainable manner. This review advocates switching to use of organic matter (manure and compost) that contains vital nutrients for plant growth and helps restore soil health. Humic substances (HSs), derived from degraded plant remains and found ubiquitously in nature, are an important source of organic matter. The application of HSs to soil enhances essential nutrient supply and assimilation of atmospheric CO2 due to increasing biomass yield. Promoting HS application globally can help lower atmospheric CO2 concentrations and create a sustainable agricultural practice. However, the process of humification and the molecular structure of HSs remain poorly understood subjects in soil science. Therefore, it is imperative to understand the mechanisms underlying various roles of HSs in agroecosystems. This review offers an insight into the various structural and functional aspects of HSs, particularly fulvic acid and humic acid. The dynamic and interactive nature of HSs creates a framework for sustainable agriculture.